2015
DOI: 10.3109/0284186x.2015.1105381
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer surgery in elderly patients: Balancing between short-term harm and long-term benefit. A population-based study in the Netherlands

Abstract: Background: At a national level, it is unknown to what degree elderly patients with pancreatic or periampullary carcinoma benefit from surgical treatment compared to their younger counterparts. We investigated resection rates and outcomes after surgical treatment among elderly patients. Methods: From the Netherlands Cancer Registry, 20 005 patients diagnosed with primary pancreatic or periampullary cancer in 2005-2013 were selected. The associations between age (570, 70-74, 75-79, 80 years) and resection rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 22 publications
6
54
1
Order By: Relevance
“…Centralisation could contribute to increases in resection rates 17. Centralisation started in the Netherlands regionally in 200518 19 and nationally in 2011,20 and in Denmark in 200021. Nationally, the number of hospitals performing pancreatoduodenectomy for PaC decreased from 39 to 23 in 2004 to 2009 in the Netherlands and the proportion of patients resected at medium/high-volume (>10 resections/year) centres increased from 53% to 91%, accompanied by an increase in pancreatoduodenectomy from 258 (11%) to 394 (18%) 17 22.…”
Section: Discussionmentioning
confidence: 99%
“…Centralisation could contribute to increases in resection rates 17. Centralisation started in the Netherlands regionally in 200518 19 and nationally in 2011,20 and in Denmark in 200021. Nationally, the number of hospitals performing pancreatoduodenectomy for PaC decreased from 39 to 23 in 2004 to 2009 in the Netherlands and the proportion of patients resected at medium/high-volume (>10 resections/year) centres increased from 53% to 91%, accompanied by an increase in pancreatoduodenectomy from 258 (11%) to 394 (18%) 17 22.…”
Section: Discussionmentioning
confidence: 99%
“…Given the role of adjuvant therapies in prolonging overall survival and delaying time to recurrence in resectable pancreatic cancer[34,35], the advancing age alone should not preclude the use of adjuvant treatment. Although these limitations, most Authors reported that overall survival after resection for pancreatic cancer in octogenarians is not statistically different from younger patients[18,21,36,37]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, we extrapolate that postoperative mortality and SES are not predictors of cancer survival. [41]…”
Section: Discussionmentioning
confidence: 99%